2012
DOI: 10.1007/s12105-012-0330-2
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Carcinoma Ex Pleomorphic Adenoma in an Adolescent Confirmed by Application of PLAG1 Immunohistochemistry and FISH for PLAG1 Rearrangement

Abstract: A 16-year-old previously asymptomatic boy presented with complaints of fatigue, weight loss, and back pain for several months. Imaging studies revealed a large superior mediastinal mass, numerous bilateral pulmonary nodules, and multiple lytic bone lesions. A needle biopsy from a sternal lesion showed a poorly differentiated carcinoma, immunoreactive for cytokeratins and EMA and immunonegative for various organ/tissue-specific markers. His past medical history was significant for excision of a parotid gland tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Tsang et al [16] reported a case of CA-ex-PA with amplification of multiple genes including PLAG1 [16]. We have also recently demonstrated increased copy number and amplification of rearranged PLAG1 in a CA-ex-PA in a young patient who had a history of PA with simple PLAG1 rearrangement [38]. An additional case in our current series showed amplification of altered PLAG1.…”
Section: Discussionsupporting
confidence: 71%
“…Tsang et al [16] reported a case of CA-ex-PA with amplification of multiple genes including PLAG1 [16]. We have also recently demonstrated increased copy number and amplification of rearranged PLAG1 in a CA-ex-PA in a young patient who had a history of PA with simple PLAG1 rearrangement [38]. An additional case in our current series showed amplification of altered PLAG1.…”
Section: Discussionsupporting
confidence: 71%
“…Interphase fluorescence in‐situ hybridization (FISH) studies were performed on 4‐μm‐thick sections of the TMA, with a custom dual‐colour, break‐apart probe for PLAG1 , and a dual‐colour, break‐apart probe for HMGA2 , as previously described . In addition, a FISH assay was designed to determine the copy number status of PLAG1 , with bacterial artificial clone RP11‐140I16, in relation to the number of copies of the chromosome 8 centromere probe.…”
Section: Methodsmentioning
confidence: 99%
“…The most common histological subtype of CXPA is salivary duct carcinoma (SDC), followed by myoepithelial carcinoma (MYC) and adenocarcinoma not otherwise specified (NOS), although CXPA can present any histological subtype of salivary gland malignant tumour . Similar to PA, PLAG1 / HMGA2 rearrangements are the most frequently observed genetic events in CXPA, and detection of PLAG1 expression or PLAG1 rearrangements are practically used to distinguish PA and CXPA from other benign or malignant salivary tumours . PLAG1 is presumed to play an important role in CXPA; however, it is poorly understood, especially in the context of CXPA morphology …”
Section: Introductionmentioning
confidence: 99%
“…1,19 Similar to PA, PLAG1/HMGA2 rearrangements are the most frequently observed genetic events in CXPA, 20 and detection of PLAG1 expression or PLAG1 rearrangements are practically used to distinguish PA and CXPA from other benign or malignant salivary tumours. 20,21 PLAG1 is presumed to play an important role in CXPA; however, it is poorly understood, especially in the context of CXPA morphology. [22][23][24] In this study, we analysed PLAG1 and HMGA2 gene fusions in PAs by reverse transcription-polymerase chain reaction (RT-PCR) and examined the relationship between the fusion genes and the clinicopathological characteristics of PAs.…”
Section: Introductionmentioning
confidence: 99%